And vegetables for all: urban and civic agriculture in Kansas City and visions for the U.S. agrifood system - Beach, Sarah S. (Kansas State University, 2013)
In the United States, many are critical of agricultural policies and economic incentives that support large-scale food production and the dominant actors in the mainstream agrifood system. Critics point out that at the same time agribusinesses and very large-scale farmers receive support, there are those in poverty who struggle to meet their food needs. Critics question what that relationship should be between civil society and the agrifood system. A variety of activities are addressing concerns of social injustices in the system. For example, participation is increasing in civic and urban agriculture. Civic agriculture is the interrelated activities of small-scale, socially and environmentally sound practices of food production and consumption that aim to increase community sustainability. Urban agriculture is food production in and near cities. By focusing on Kansas and the Kansas City metropolitan area, this dissertation addresses the following questions: How do the relations between civil society and the U.S. agrifood system impact the level of fairness in the system? To what extent are urban agricultural activities fostering fairness in the agrifood system, including access to fresh foods, civic engagement, and fulfilling careers, while also benefiting the environmental health of the city? Survey and interview data collected by a research team on agriculture in Kansas sets the context for my examination of urban agriculture in Kansas City’s urban core. In addition to participant observations and primary and secondary data analysis, I conducted 38 semi-structured interviews with growers (27), food advocates (4), community organizers (4), and governmental employees (3). In Kansas City, many of the activities and programs in place are building community, strengthening civil society, and promoting food justice for the poor and for people of color, for example, in food deserts, which are locales where people particularly face challenges in meeting their food needs. While some participants are more focused on their immediate communities and less so on overt widespread change, others feel a part of a social movement aiming to change the agrifood system. Diverse people from various social classes and races are increasingly becoming involved in growing food and food advocacy to expand fairness in the system.
Keywords: Urban agriculture; Civic agriculture; Food access; Kansas City; Civil society; Civic engagement; Sociology (0626)